2004
DOI: 10.1103/physreva.69.062102
|View full text |Cite
|
Sign up to set email alerts
|

Correction to the Casimir force due to the anomalous skin effect

Abstract: The surface impedance approach is discussed in connection with the precise calculation of the Casimir force between metallic plates. It allows to take into account the nonlocal connection between the current density and electric field inside of metals. In general, a material has to be described by two impedances $Z_{s}(\omega,q)$ and $Z_{p}(\omega,q)$ corresponding to two different polarization states. In contrast with the approximate Leontovich impedance they depend not only on frequency $\omega$ but also on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 52 publications
5
100
0
4
Order By: Relevance
“…For the anomalous skin effect these impedances were found in [30] (see also [27]). When q → 0 (propagating field) both impedances coincide and reproduce the Leontovich impedance for the anomalous skin effect [33].…”
Section: Entropy In the Low-temperature Limitmentioning
confidence: 99%
See 2 more Smart Citations
“…For the anomalous skin effect these impedances were found in [30] (see also [27]). When q → 0 (propagating field) both impedances coincide and reproduce the Leontovich impedance for the anomalous skin effect [33].…”
Section: Entropy In the Low-temperature Limitmentioning
confidence: 99%
“…We stressed [25,27] that to analyse the low-temperature behaviour one has to take into consideration the anomalous skin effect. Description of nonlocal metals can be done with two nonlocal dielectric functions [26] or equivalently with two impedances [30], which are known in the theory of metals. It was demonstrated that the Leontovich impedance, which is used for the description of propagating fields, cannot be applied for the Casimir problem because evanescent fields are important in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lifshitz result for two parallel semi-infinite dielectrics separated by a vacuum slit is obtained from (25) when Fresnel coefficients r T M (iω, k), r T E (iω, k) are substituted into (25) [6,22]. The limit ε(iω) → +∞ corresponds to reflection coefficients of a perfectly conducting metal plane: r T M = +1, r T E = −1.…”
Section: Free Energymentioning
confidence: 99%
“…Contribution of T M part is obtained in full analogy. Free energy has the form (25) ω n = 2πnT are Matsubara frequencies, prime means n = 0 term is taken with the coefficient 1/2, r…”
Section: Free Energymentioning
confidence: 99%